The ability of K. pneumoniae isolated from nosocomial infections to the synthesis of β-lactamase - S. A. Atakishizadeh (Детские инфекции (Москва))
In recent years, there has been an increase in bacterial strains capable of synthesizing extended-spectrum β-lactamase (ESBL).The study examined the ability of K. pneumoniae strains isolated from 30 patients in the surgical ward with urinary tract infections (1 8), from the areas of surgical intervention (7) and nosocomial pneumonia (5). Synthesis of ESBL K. pneumoniae was detected by means of a phenotypic test and using two disks.The ESBL-positive K. pneumoniae was found in 40% of the isolated nosocomial strains. It was established that ESBL-positive strains of K. pneumoniae were significantly more often (p <0.05) isolated from infections in the area of surgical intervention and pneumonia (86% and 60%, respectively).